Improvement in XIa Selectivity of Snake Venom Peptide Analogue BF9-N17K Using P2′ Amino Acid Replacements - Li Ding; Zhiping Zhai; Tianxiang Qin; Yuexi Lin; Zhicheng Shuang; Fang Sun; Chenhu Qin; Hongyi Luo; Wen Zhu; Xiangdong Ye; Zongyun Chen; Xudong Luo (Toxins)
Coagulation factor XIa is a new serine-protease family drug target for next-generation anticoagulants. With the snake venom Kunitz-type peptide BF9 as the scaffold, we obtained a highly active XIa inhibitor BF9-N17K in our previous work, but it also inhibited the hemostatic target plasmin. Here, in order to enhance the selectivity of BF9-N17K toward XIa, four mutants, BF9-N17K-L19A, BF9-N17K-L19S, BF9-N17K-L19D, and BF9-N17K-L19K, were further designed using the P2′ amino acid classification scanning strategy. The anticoagulation assay showed that the four P2′ single-point mutants still had apparent inhibitory anticoagulation activity that selectively inhibited the human intrinsic coagulation pathway and had no influence on the extrinsic coagulation pathway or common coagulation pathway, which indicated that the single-point mutants had minimal effects on the anticoagulation activity of BF9-N17K. Interestingly, the enzyme inhibitor assay experiments showed that the XIa and plasmin inhibitory activities were significantly changed by the P2′ amino acid replacements. The XIa inhibitory activity of BF9-N17K-L19D was apparently enhanced, with an IC50 of 19.28 ± 2.53 nM, and its plasmin inhibitory was significantly weakened, with an IC50 of 459.33 ± 337.40 nM. BF9-N17K-L19K was the opposite to BF9-N17K-L19D, which had enhanced plasmin inhibitory activity and reduced XIa inhibitory activity. For BF9-N17K-L19A and BF9-N17K-L19S, no apparent changes were found in the serine protease inhibitory activity, and they had similar XIa and plasmin inhibitory activities to the template peptide BF9-N17K. These results suggested that the characteristics of the charge of the P2′ site might be associated with the drug selectivity between the anticoagulant target XIa and hemostatic target plasmin. In addition, according to the molecular diversity and sequence conservation, a common motif GR/PCR/KA/SXIP-XYGGC is proposed in the XIa-inhibitory Kunitz-type peptides, which might provide a new clue for further peptide engineering. In conclusion, through P2′ amino acid classification scanning with the snake venom Kunitz-type peptide scaffold, a new potent and selective XIa inhibitor, BF9-N17K-L19D, was discovered, which provides a new XIa-targeting lead drug template for the treatment of thrombotic-related diseases.